2016
DOI: 10.2147/jpr.s117451
|View full text |Cite
|
Sign up to set email alerts
|

Local anesthesia for pain control during transrectal ultrasound-guided prostate biopsy: a systematic review and meta-analysis

Abstract: BackgroundA meta-analysis was performed to evaluate the efficacy and safety of intrarectal local anesthestic (IRLA), periprostatic nerve block (PPNB), and the combined modalities in alleviating the pain during transrectal ultrasound (TRUS)-guided prostate biopsy.Materials and methodsA literature review was performed to identify all published randomized controlled trials (RCTs) about IRLA vs no anesthesia or placebo gel; PPNB vs no injection, periprostatic placebo injection, or IRLA; combined PPNB and IRLA vs P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 35 publications
3
15
0
1
Order By: Relevance
“…In both groups, the most painful step revealed to be the insertion of the probe into the rectum. A recent systematic review revealed that the administra-tion of intrarectal anesthetic gel followed by PNB led to a lower degree of pain both during probe movements and needle piercing but had no remarkable effect on the pain experienced during the insertion of the probe (17). Urabe et al compared the effectivity of intrarectal local anesthetic, PNB, and the combined methods in alleviating the pain during TRUS-guided SPB and reported that PNB led to lower pain levels during the insertion of the probe compared to other techniques (18).…”
Section: Discussionmentioning
confidence: 99%
“…In both groups, the most painful step revealed to be the insertion of the probe into the rectum. A recent systematic review revealed that the administra-tion of intrarectal anesthetic gel followed by PNB led to a lower degree of pain both during probe movements and needle piercing but had no remarkable effect on the pain experienced during the insertion of the probe (17). Urabe et al compared the effectivity of intrarectal local anesthetic, PNB, and the combined methods in alleviating the pain during TRUS-guided SPB and reported that PNB led to lower pain levels during the insertion of the probe compared to other techniques (18).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of PPNB and PPNB + IRLA showed that probe manipulations were less painful in patients who received PPNB alone, while the PPNB + IRLA group experienced less pain when the needle contacted the prostate (16). When the patients in our study were asked which stage of the procedure was most painful, they said it was insertion of the rectal probe ( Figure 1).…”
Section: Discussionmentioning
confidence: 86%
“…According to the findings of Alavi et al (15), PPNB with lidocaine was more advantageous compared with IRLA alone. In a meta-analysis comparing PPNB and IRLA with their combination, it was reported that the combination was more effective at controlling pain compared to IRLA or PPNB alone (16). There are numerous studies demonstrating that PPNB is effective in pain control during TRUS-guided prostate biopsy (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…The current standard PBx, using 10–14 biopsy cores, detects PCa in about 44% of patients, and it is estimated that 2.5 million procedures are performed each year worldwide [2]. Notably, patients undergoing PBx are under considerable psychological stress due to the potential for a cancer diagnosis, fear of anal penetration, and the pain induced by both probe insertion and core biopsy [3].…”
Section: Introductionmentioning
confidence: 99%